2009
DOI: 10.1002/nur.20335
|View full text |Cite
|
Sign up to set email alerts
|

Social support, life stress, and anxiety as predictors of pregnancy complications in low‐income women

Abstract: Prospective repeated measures were used to examine attachment, social support, life stress, anxiety, and psychological wellbeing among low-income women in early and late pregnancy and the relationships of these variables to prenatal, intrapartum, and neonatal complications. One hundred and eleven medically healthy, low-income, Medicaid-eligible women ages 18-35 years, between 14 and 22 weeks of pregnancy were recruited from prenatal clinics. Self-report questionnaires and hospital records were used to collect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 64 publications
(68 reference statements)
2
38
1
Order By: Relevance
“…37 In addition, we found the mean anxiety levels in our sample (STAI mean = 34) were similar to other reports from low–income, predominately African American pregnant women (STAI mean = 39). 38 Other researchers have found that women with low levels of social support also reported higher levels of prenatal depressive symptoms. 39,40 Specifically, the social support of the infant’s father has been identified as a protective factor for elevated postpartum depressive symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…37 In addition, we found the mean anxiety levels in our sample (STAI mean = 34) were similar to other reports from low–income, predominately African American pregnant women (STAI mean = 39). 38 Other researchers have found that women with low levels of social support also reported higher levels of prenatal depressive symptoms. 39,40 Specifically, the social support of the infant’s father has been identified as a protective factor for elevated postpartum depressive symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…Family pressure ---0.14 (-9.70 to 9.98) 0.078 researches indicate the highness of stress level among those who do not have sufficient income for supplying their expenses (25)(26)(27)(28). One of the other predictors of perceived stress was the method of received treatment such that perceived stress among women who received two treatments of Intrauterine insemination and ovulation simultaneously was higher than the perceived stress among those who have done other treatment methods like Intra-uterine insemination or IVF and probably the highness of multiple treatment expenses or being worried of the failure of a more effective method can justify this higher stress among people.…”
Section: Cause Of Treatmentmentioning
confidence: 99%
“…The current body of literature suggests that low income women with unexpected pregnancy are more prone to high level of stress, depression and anxiety (Zachariah, 2009). Siegel and Brandon (2014) in a recent review of the literature reported that the rates of perinatal depressive symptoms in adolescents are higher than pregnant adults (Siegel & Brandon, 2014).…”
Section: Discussionmentioning
confidence: 99%